Meningkatkan Kemampuan Kosakata Bahasa Inggris Melalui Mind Map pada Siswa Kelas VII - Rahmat, Andi Dzul (Indonesian Journal of Pedagogical and Social Sciences, 2023)
Abstract. This study aims to increase English vocabulary through a Mind Map in class VII.5 students of SMPN 23 Makassar for the 2022/2023 academic year. This research was conducted in two cycles and each cycle consisted of two meetings and each meeting consisted of planning, action, observation and reflection stages. The results showed that from the pre-action the percentage of English vocabulary mastery was 20 students or 65%, cycle I increased by 22 students or 71%, and in cycle II it increased by 25 students or 81%. The results of this study indicate that English vocabulary can be increased through a Mind Map in class VII.5 students of SMPN 23 Makassar for the 2022/2023 academic year. Keywords: Vocabulary, Mind Map, English Language